2020
DOI: 10.3390/nu12082288
|View full text |Cite
|
Sign up to set email alerts
|

Underlying Susceptibility to Eating Disorders and Drug Abuse: Genetic and Pharmacological Aspects of Dopamine D4 Receptors

Abstract: The dopamine D4 receptor (DRD4) has a predominant expression in the prefrontal cortex (PFC), brain area strictly involved in the modulation of reward processes related to both food and drug consumption. Additionally, the human DRD4 gene is characterized by a variable number of tandem repeats (VNTR) in the exon 3 and, among the polymorphic variants, the 7-repeat (7R) allele appears as a contributing factor in the neurobiological mechanisms underlying drug abuse, aberrant eating behaviors and related comorbiditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 266 publications
(354 reference statements)
0
31
0
Order By: Relevance
“…Splice variants are mainly described for the D 2 and the D 4 receptors; importantly, other gene polymorphisms described for all five receptors, including single nucleotide polymorphism, may be associated with a variety of addictions (drugs, alcohol, etc.) and obesity [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]; other non-dopamine-receptor-related factors also influence addictive behaviors.…”
Section: Dopamine Dopamine Receptors and Catechol-related Enzymesmentioning
confidence: 99%
See 1 more Smart Citation
“…Splice variants are mainly described for the D 2 and the D 4 receptors; importantly, other gene polymorphisms described for all five receptors, including single nucleotide polymorphism, may be associated with a variety of addictions (drugs, alcohol, etc.) and obesity [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]; other non-dopamine-receptor-related factors also influence addictive behaviors.…”
Section: Dopamine Dopamine Receptors and Catechol-related Enzymesmentioning
confidence: 99%
“…Both imbalances in dopamine neurotransmission and alterations of brain circuits where dopamine is a key factor are involved in a variety of neurological and neuropsychiatric diseases, from alcohol/drug addiction to schizophrenia [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 59 , 60 , 61 , 62 ]. In fact, typical antipsychotics act “almost exclusively on the dopamine system” [ 63 ].…”
Section: Dopamine L-dopa and Parkinson’s Diseasementioning
confidence: 99%
“…Regarding the ligands of the D1 and D2 receptors (agonists, antagonists, and partial agonists), selective compounds with new pharmacological targets in relation to the interactions with the dopamine-glutamate systems have been experimented in different diseases; this may lead to the discovery of a drug suitable for addressing the complexity of dopamine receptors' hetero-complexes in native systems using multiple intra-cell markers and benefiting from more selective tools available for studying the dopamine receptors [125]. In particular, the DRD4 receptor, which is part of the D2-like family, has a predominant expression in the prefrontal cortex (PFC), a brain area closely involved in the modulation of reward processes related to both food and drug consumption [126]. Several human studies have revealed a possible involvement of DRD4 in eating disorders and obesity [126].…”
Section: Dopamine Receptorsmentioning
confidence: 99%
“…In particular, the DRD4 receptor, which is part of the D2-like family, has a predominant expression in the prefrontal cortex (PFC), a brain area closely involved in the modulation of reward processes related to both food and drug consumption [126]. Several human studies have revealed a possible involvement of DRD4 in eating disorders and obesity [126]. Hence, DRD4 is an important pharmacological target to be explored for innovative selective drugs in the treatment of addictive disturbances such as eating disorders and related comorbidities [126].…”
Section: Dopamine Receptorsmentioning
confidence: 99%
See 1 more Smart Citation